Ion transport: electrical characterization of CFTR in epithelia and computational modeling of action potential - Lee, Dongoh (My University, 2026)
Maneuvering efficient ion transport between cells is crucial to maintain proper cellular activity and function. Transporting ions across the cell membrane requires dedicated proteins that mediate specific ion conduction. Physicochemical fundamentals rule this ion flow through channels and transporters. Driving force (voltage) and Nernst potential that govern ion flow (current flux) are regulated by channel gating, which determines conductance. Charge accumulation (capacitance) within polarized epithelia is traditionally regarded as exhibiting surface area but also indicative of dampens and buffering ion flux. Cystic fibrosis (CF) is devastating disease that compromised with mucus plug in airway and impaired enzymatic juice secretion in pancreas. Malfunctional cystic fibrosis transmembrane conductance regulator (CFTR) channel fails to secrete chloride and bicarbonate cause unbalanced lumen environment. We conducted series of works to identify the relative bicarbonate conductance because CFTR controlled lumen pH was major key factor for contributing CF symptoms. Overexpressed human CFTR variants (wild type, G551D, and F508del) on FRT cells with different anion concentrations demonstrated that conductance had a correlated to anion concentration (100 Cl⁻, 100 Cl⁻ + 25 HCO₃⁻, and 125 Cl⁻). Furthermore, their relationship ratio was different depending on stimulant (forskolin, forskolin + VX770, forskolin + VX445). We assessed relative bicarbonate conductance by comparing 25 mM surplus bicarbonate and chloride conductance. VX770 enhanced chloride and bicarbonate conductance in all three variants, but not the relative bicarbonate to chloride conductance ratio. Wild type and F508del with both correctors presented relative bicarbonate to chloride conductance ratio as 0.1 and 0, respectively. Chronic exposure VX445 further enhanced relative bicarbonate to chloride conductance ratio up to 0.2 in wild type. G551D had relative bicarbonate to chloride conductance ratio 0.2 and following VX445 further enhanced it. To investigate the relative bicarbonate to chloride conductance of CFTR in naturally CFTR expressing polarized epithelia, we conducted similar setup in pig vas deferens (PVD9902). Electrochemical impedance spectroscopy (EIS) evaluated distinct apical and basolateral conductance by obtaining two semi-circle Nyquist plot. Overall electrical properties of PVD9902 were assessed with both side capacitance and transepithelial voltage. Forskolin/IBMX induced both correctors pretreated pig CFTR associated relative bicarbonate to chloride conductance ratio was higher than 2. Following VX770 reduced this ratio down to 1. Basolateral DNDS treatment likely blocked NBC completely impaired this ratio further down to 0. High basolateral conductance presence of bicarbonate, more sensitive to DNDS, indicative of anion channel with highly permeant to bicarbonate. Hyperpolarizing transepithelial voltage (Vte) and increment of static capacitance (Cs) suggested that augmented anion flux throughout forskolin and VX770. Presence of bicarbonate providing more hyperpolarized Vte and less Cs suggested efficient discharge of ion. Gradually uprising of apical capacitance (Ca) with forskolin/IBMX involved accumulation of charge near the cell surface. Different time constant and delta capacitance between bicarbonate and chloride suggested that Ca contributed by exocytosis mediated surface increment and additional accumulation of charge near the surface. Basolateral capacitance (Cb) also appeared differently affected by anion. Dynamic ion permeability contributes to membrane potential in GHK voltage equation. Ever since discovery of characteristic potassium and sodium conductance illuminated neuronal activity by Hodgkin and Huxley, their equations adapted widely to simulate the action potential. We modified GHK equations to employ conductance and Markov model represented each channel state. Voltage gated channels organized into four states (close, open, inactive_one, and inactive_two) with voltage sensitive kinetic parameters and permeant to potassium, sodium, and calcium. Ligand gated channels were composed of monovalent cation and chloride with two states (close, open). Computational activation and fast inactivation voltage clamp represented broad KV 2.1 and NaV 1.6 profiles with modified GHK current equation. Action potential spike was observed when cation channel initiated small conductance was higher than threshold of NaV. Following delayed KV activation repolarized and hyperpolarized membrane potential returning to resting membrane potential. Refractory time was observed due to relatively slow inactivation kinetic of NaV. Activation of chloride channel where Nernst potential was below resting membrane potential inhibited action potential generation. In conclusion, we provided another insight to understand ion transport in non-excitable cell and excitable cell with experiment and computational simulation. Polarized epithelia behaves differently than floating single cell and its primary purpose is to deliver/absorb selectively for optimal cellular function. Ion channel location and its contribution to establishing voltage across the membrane is related to adjunct ion concentration. Their ion selective conductance can be varied with drugs.
Keywords: Electrophysiology; Cystic fibrosis transmembrane conductance regulator; Ion transport; Action potential